Shared Multimodal Input Through Social Coordination: Infants With Monolingual and Bilingual Learning Experiences - Sun, Lichao; Griep, Christina D.; Yoshida, Hanako (Frontiers in Psychology, 2022)
A growing number of children in the United States are exposed to multiple languages at home from birth. However, relatively little is known about the early process of word learning—how words are mapped to the referent in their child-centered learning experiences. The present study defined parental input operationally as the integrated and multimodal learning experiences as an infant engages with his/her parent in an interactive play session with objects. By using a head-mounted eye tracking device, we recorded visual scenes from the infant’s point of view, along with the parent’s social input with respect to gaze, labeling, and actions of object handling. Fifty-one infants and toddlers (aged 6–18 months) from an English monolingual or a diverse bilingual household were recruited to observe the early multimodal learning experiences in an object play session. Despite that monolingual parents spoke more and labeled more frequently relative to bilingual parents, infants from both language groups benefit from a comparable amount of socially coordinated experiences where parents name the object while the object is looked at by the infant. Also, a sequential path analysis reveals multiple social coordinated pathways that facilitate infant object looking. Specifically, young children’s attention to the referent objects is directly influenced by parent’s object handling. These findings point to the new approach to early language input and how multimodal learning experiences are coordinated socially for young children growing up with monolingual and bilingual learning contexts.